Mosquito long non-coding RNAs are enriched with Transposable Elements - Elverson Soares de Melo; Gabriel Luz Wallau (Genetics and Molecular Biology, 2022)
Abstract Long non-coding RNAs (lncRNAs) lack coding capacity and mounting evidence suggests that they have a regulatory role in diverse organisms. Most knowledge about lncRNAs comes from studies on vertebrates, including a structural association between lncRNAs and transposable elements (TEs). TE sequences are genomic parasites found in all branches of life and are particularly active and abundant in insect genomes. Here we investigate the contribution of TEs to lncRNA biogenesis in Aedes albopictus and Culex quinquefasciatus. We found that a large fraction of lncRNA loci co-occurs with TE loci in both species. Around 40% of A. albopictus and 52% of C. quinquefasciatus lncRNAs show some association with TEs. Most of the lncRNA/TE associations are represented by TE-derived sequences that are expressed as one or all exons of lncRNAs, including five lncRNAs that seem to influence immune-related genes involved in antiviral response. The contribution of TEs to lncRNAs also varies among the different types of TEs. The Gypsi superfamily is particularly enriched in lncRNAs sequences. In sum, this study demonstrates that transposable elements substantially contribute to lncRNAs biogenesis in A. albopictus and C. quinquefasciatus and may have an impact on regulatory modulation in these species.